Benchmarking the performance and practices of the DOST-PEZA Open TBI - Gonzales, Cherry G. author (University of the Philippines Diliman, Technology Management Center, 2014)
This study aimed to benchmark the performance of DOST-PEZA Open TBI against TBI's in other countries. Following the 2008 study of Tecsult, Inc., the business model of the Open TBI was compared with 17 foreign incubators, in terms of general characteristics, team and network, selection process and criteria, services offered, coaching, follow-up with graduates, business development, client sources, allocation of efforts and financial structure. Primary performance indicators were collected wherein secondary performance indicators were drawn to offset differences in size and operating budget of the incubators. This study mostly employed descriptive analysis in making the comparison. After comparing the characteristics of the Open TBI with selected foreign TBI's, it was found that six practices out of the ten dimensions of business model were associated with high performance of selected incubators. This includes having a generalist and mixed incubator, a team with high level of expertise and diverse training, sufficient budget regardless of the source, formal and structured selection process, more financial service offering, systematized but flexible coaching and availability of start-up funding. Of the said best practices, the Open TBI fared well in terms of selection process. To gain more understanding about the environment surrounding the Open TBI, the economic and organizational context was briefly described using the innovation system approach at three levels. At the macro-level of innovation is the Philippine National Innovation System. At the meso-level is the DOST-PEZA Open TBI wherein the incubator serves as an intermediary between the elements of macro and micro-level of innovation. At the micro-level is the innovation system of client and graduate firms of the said incubator. As learned through the benchmarking study, success is a result of combination of variables in a system and it cannot be attributed to one single practice. There is no hard fast rule in best practice because the contextual environmental differs. It is therefore important to strike a balance considering the elements of the innovation system.